Prognostic value of the immediate response to surfactant. Issue 3 (November 1994) - Kuint, J; Reichman, B; Neumann, L; Shinwell, E S
Abstract : AIM--To evaluate the association between the immediate response to surfactant treatment and morbidity and mortality in infants with severe respiratory distress syndrome. METHODS--The response to surfactant was defined as the difference in the arterial:alveolar (delta a:A) ratio before and one hour after the first surfactant dose. Measurements were obtained from 253 Israeli infants participating in the multi-centre Curosurf 4 trial of surfactant replacement therapy. RESULTS--Delta a:A ratios ranged from -0.115 to 0.8 and were significantly related to both birth weight and gestational age. Among infants weighing 1001-1500 g mortality decreased from 40% among very bad responders to zero among good responders. The incidence of pneumothorax decreased with better response. Logistic regression analysis showed a hierarchy of predictive power for mortality: birth weight or gestational age; immediate response to surfactant; severity of initial disease. CONCLUSION--The immediate response to surfactant treatment is a significant prognostic indicator for mortality and morbidity.